2018
DOI: 10.3847/1538-3881/aabded
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-year Search for Transits of Proxima Centauri. I. Light Curves Corresponding to Published Ephemerides

Abstract: Proxima Centauri has become the subject of intense study since the radial-velocity discovery by Anglada-Escudé et al. (2016) of a planet orbiting this nearby M-dwarf every ∼ 11.2 days. If Proxima Centauri b transits its host star, independent confirmation of its existence is possible, and its mass and radius can be measured in units of the stellar host mass and radius. To date, there have been three independent claims of possible transit-like event detections in light curve observations obtained by the MOST sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It hosts the nearest exoplanet, Proxima b (Anglada-Escudé et al 2016), a telluric mass planet with a very short orbital period (11.2 d) and orbital distance (0.05 au) that place it inside the habitable zone of its parent star. The search for transiting exoplanet signals have been unsuccessful up to now (Blank et al 2018;Feliz et al 2019). Proxima is an active star, with frequent flares that were detected over a broad range of wavelengths (MacGregor et al 2018;Howard et al 2018).…”
Section: Proximamentioning
confidence: 99%
“…It hosts the nearest exoplanet, Proxima b (Anglada-Escudé et al 2016), a telluric mass planet with a very short orbital period (11.2 d) and orbital distance (0.05 au) that place it inside the habitable zone of its parent star. The search for transiting exoplanet signals have been unsuccessful up to now (Blank et al 2018;Feliz et al 2019). Proxima is an active star, with frequent flares that were detected over a broad range of wavelengths (MacGregor et al 2018;Howard et al 2018).…”
Section: Proximamentioning
confidence: 99%
“…TERMS, and other similar efforts, have thoroughly ruled out transits for the exoplanet hosts GJ 581 (e.g. (Kane et al 2011c), and Proxima Cen b (e.g., Kipping et al 2017;Blank et al 2018). However, resources for individual efforts such as those listed here are limited.…”
Section: Monte Carlo Simulations Of Transit Probabilitymentioning
confidence: 99%
“…Using the Bright Star Survey Telescope in Antartica, Liu et al (2018) report a number of transit-like events that could be ascribed to Proxima b, and assuming large transit timing variations (TTV), they could phase with the event reported in Kipping et al (2017). On the contrary, Blank et al (2018) were unable to confirm any of the previously reported transit events using optical data spanning 11 years, albeit with heterogeneous and noncontinuous data sets. They do, however, confirm the impact of high stellar activity on optical light curves.…”
Section: Introductionmentioning
confidence: 87%